Identification of PDGFRα-positive interstitial cells in the distal segment of the murine vas deferens - Tasuku Hiroshige (Nature Portfolio, 2021)
Abstract Platelet-derived growth factor receptor-α (PDGFRα)-positive interstitial cells (ICs) are widely distributed in various organs and may be involved in the motility of various tubular organs. We, for the first time, aimed to investigate the distribution, immunohistochemical characteristics, and ultrastructure of PDGFRα-positive ICs in murine vas deferens, using confocal laser scanning microscopy, transmission electron microscopy (TEM), and immuno-electron microscopy (immuno-EM). For immunofluorescence, we used antibodies against PDGFRα and other markers of ICs. PDGFRα-positive ICs were distributed widely in the lamina propria, smooth muscles, and serosal layers. Although most PDGFRα-positive ICs labeled CD34, they did not label CD34 in the subepithelial layers. Additionally, PDGFRα-positive ICs were in close proximity to each other, as also to the surrounding cells. TEM and immuno-EM findings revealed that PDGFRα-positive ICs established close physical interactions with adjacent ICs. Extracellular vesicles were also detected around the PDGFRα-positive ICs. Our morphological findings suggest that PDGFRα-positive ICs may have several subpopulations, which can play an important role in intercellular signaling via direct contact with the IC network and the extracellular vesicles in the murine vas deferens. Further investigation on PDGFRα-positive ICs in the vas deferens may lead to understanding the vas deferens mortility.